2019
DOI: 10.1038/s41467-019-09562-7
|View full text |Cite
|
Sign up to set email alerts
|

Lower synaptic density is associated with depression severity and network alterations

Abstract: Synaptic loss and deficits in functional connectivity are hypothesized to contribute to symptoms associated with major depressive disorder (MDD) and post-traumatic stress disorder (PTSD). The synaptic vesicle glycoprotein 2A (SV2A) can be used to index the number of nerve terminals, an indirect estimate of synaptic density. Here, we used positron emission tomography (PET) with the SV2A radioligand [ 11 C]UCB-J to examine synaptic density in n = 26 unmedicated indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
264
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 340 publications
(280 citation statements)
references
References 76 publications
(102 reference statements)
13
264
2
1
Order By: Relevance
“…Third, medication effects cannot be ruled out as contributing to the current results, although brain penetrative medications were not administered for an average of 13 hours before PET measurements, and medications affecting SV2A were exclusionary criteria. Fourth, although we interpret SV2A differences as evidence of synaptic decreases, as noted recently, other interpretations are possible (eg, synaptic vesicle dysfunction and/or cycling). Preclinical work has shown, however, that synaptic vesicle pools are stable within synapses .…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Third, medication effects cannot be ruled out as contributing to the current results, although brain penetrative medications were not administered for an average of 13 hours before PET measurements, and medications affecting SV2A were exclusionary criteria. Fourth, although we interpret SV2A differences as evidence of synaptic decreases, as noted recently, other interpretations are possible (eg, synaptic vesicle dysfunction and/or cycling). Preclinical work has shown, however, that synaptic vesicle pools are stable within synapses .…”
Section: Discussionmentioning
confidence: 60%
“…53 Last, it should be noted that other studies have used similar methodology with SV2A imaging at our center and also found disease-specific differences in SV2A in epilepsy, Alzheimer disease, and major depressive disorder. 12,29,35 Thus, emerging regional patterns in these diseases foster interest in the utility of SV2A as a wide-ranging neuropsychiatric biomarker for diagnosis, disease progression, and possibly treatment monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence from human brain imaging studies suggests that major depressive disorder is associated with reduced synaptic connections, which are likely linked to the observed differences in network functional connectivity 72 . The long-standing theory for how stressful experience alters mPFC dendritic spines and synapses is shaped as an inverse parabolic function.…”
Section: Discussionmentioning
confidence: 99%